2013
DOI: 10.1007/s00441-013-1592-z
|View full text |Cite
|
Sign up to set email alerts
|

REG gene expression in inflamed and healthy colon mucosa explored by in situ hybridisation

Abstract: The regenerating islet-derived (REG) gene family encodes a group of proteins highly expressed in several human pathologies, many of which are associated with epithelial inflammation. All human family members, namely REG1A, REG1B, REG3A and REG4, are closely related in genomic sequence and all are part of the c-type lectin superfamily. REGs are highly expressed during inflammatory bowel disease (IBD)-related colonic inflammation and the in vivo expression pattern of REG1A and REG4 has been localised by using im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 24 publications
5
63
0
Order By: Relevance
“…[15][16][17] Analysis of cell source of Reg proteins in the human gut revealed that metaplastic Paneth cells in both un-inflamed samples from IBD patients and in inflamed colonic mucosa express Reg1a, Reg1b and Reg3a mRNA. 18 Elevated levels of Reg3a have also been documented in plasma samples of patients with gastrointestinal graft-versus host disease (GVHD), and the concentrations of this biomarker at onset of GVHD seem to predict response to treatment and correlate with severity of mucosal denudation. 19 Altogether these findings suggest that intestinal barrier damage, independently of the underlying cause, can permit Reg3a to traverse into the systemic circulation.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Analysis of cell source of Reg proteins in the human gut revealed that metaplastic Paneth cells in both un-inflamed samples from IBD patients and in inflamed colonic mucosa express Reg1a, Reg1b and Reg3a mRNA. 18 Elevated levels of Reg3a have also been documented in plasma samples of patients with gastrointestinal graft-versus host disease (GVHD), and the concentrations of this biomarker at onset of GVHD seem to predict response to treatment and correlate with severity of mucosal denudation. 19 Altogether these findings suggest that intestinal barrier damage, independently of the underlying cause, can permit Reg3a to traverse into the systemic circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies have disputed this, showing that ileal a-defensin loss is associated with loss of Paneth cells due to inflammatory tissue damage, and not as direct result of NOD2 loss-of-function variants [98,103,104]. These latter observations correlate well with the remarkable increase in a-defensin expression seen in colitis, suggesting that metaplastic Paneth cells are fully capable of producing a-defensin [19,86]. Another genetic variant associated with IBD is in the autophagy-related protein 16-1 (ATG16L1) loci.…”
Section: Barrier Function In Ibdmentioning
confidence: 63%
“…While usually associated with the small intestine, metaplastic Paneth cells are also found in the crypt bases of the ascending colon. Paneth cell metaplasia of proximal colon has previously been associated with long-standing colitis, but has also been observed in newly diagnosed pediatric IBD as well as in pseudomembraneous colitis [17][18][19]. Although their main function has been seen as producer of AMPs, recent research has shown that these multifaceted cells contribute in several other ways to the maintenance of intestinal homeostasis.…”
Section: The Intestinal Epitheliummentioning
confidence: 94%
“…One of the anti-inflammatory proteins induced is Reg3g, an antibacterial C-type lectin (45) that segregates the microbiota from the mucosal intestinal surface (62) and displays bactericidal activities selective for gram-positive bacteria (7). Reg3g is induced in IBD (44,63). However, this novel homeostatic equilibrium is insufficient to control DSS-induced colitis.…”
Section: Discussionmentioning
confidence: 97%